Correlational Study of Motivation and Learning Strategies After GROVE_ALPHA Implementation from a Self-Regulated Learning Perspective - Vania Valda; Irma Rahma Suwarma; Endi Suhendi (Postgraduate, University of Mataram, 2025)
This study investigates the relationship between students’ goal orientations (intrinsic and extrinsic) and their use of self-regulated learning strategies following the implementation of GROVE-ALPHA, a gamified, AI-supported formative assessment tool for physics learning. A mixed-methods sequential explanatory design was used, involving 20 high school students for the quantitative phase and follow-up interviews with 8 participants. Quantitative data were collected using the Motivated Strategies for Learning Questionnaire (MSLQ), focusing on intrinsic and extrinsic goal orientation, critical thinking, metacognitive self-regulation, and effort regulation. Kendall’s tau correlation analysis indicated that intrinsic goal orientation was more strongly associated with all three self-regulated learning strategies—especially effort regulation (τ(20)= .63, p < .001)—than extrinsic goal orientation (τ(20)= .49, p < .001). Qualitative findings supported the quantitative results, highlighting that intrinsically motivated students demonstrated greater engagement, persistence, and reflective thinking when interacting with the GROVE-ALPHA system. In contrast, extrinsically motivated students showed inconsistent engagement and shallower learning strategies. These findings suggest that integrating gamification and AI in formative assessment can support students’ self-regulated learning, particularly by strengthening intrinsic motivation. The study contributes to understanding how digital tools can influence motivation types and learning behaviors in science education.